Primary Cervical Carcinosarcoma: Report of a Rare Case - Tsatsaris, Georgios; Fasoulakis, Zacharias; Koutras, Antonios; Ntounis, Thomas; Samara, Athina A.; Syllaios, Athanasios; Diamantis, Alexandros; Kouroupi, Maria; Stamos, Charilaos; Kontomanolis, Emmanuel N. (The Surgery Journal, 2022)
Background Carcinosarcomas are malignant mixed Müllerian tumors (MMMT), containing both epithelial and mesenchymal components. Carcinosarcomas of the uterine cervix comprise an extremely rare histopathological entity, with less than 150 cases reported in the literature to date.Materials and Methods A 79-year-old postmenopausal female patient was referred to our gynecological department due to a pelvic mass and vaginal bleeding. A cervical curettage was performed and the histological report revealed a malignant neoplasm with high cellularity consisting of two components; the first was a chondrosarcoma and the latter a adenocarcinoma. A diagnosis of MMMT was confirmed through immunohistochemical (IHC) staining. Neoadjuvant chemotherapy and radiotherapy were implemented, and a year later the patient underwent a radical hysterectomy and oncological pelvic lymph node dissection. She remains disease-free 12 months postoperatively.Conclusion Primary cervical carcinosarcomas are extremely rare tumors demonstrating a bipartite profile. Preoperative diagnosis with appropriate immunochemistry testing of this rare entity is crucial to decision making.
Keywords: carcinosarcoma; cervical cancer; malignant mixed Müllerian tumors